APPLICATION OF â DISCOVERY LEARNINGâ LEARNING STRATEGY IN IMPLEMENTATION OF BASIC MICROBIOLOGY COURSEâS PRACTICE TO INCREASE 21ST CENTURY SKILL ON COLLEGE STUDENT OF BIOLOGY EDUCATION PROGRAM - Sayuti, Irda (Proceeding 7th International Seminar on Regional Education, 2015)
Abstrak There was conducted Class Action Research which purpose is to increase 21st century skill on Basic Microbiology course by applying Discovery Learning learning strategy. This research took 6 months to conduct, from September 2014 to February 2015 and whose subjects are 20 college students of Biology Education Program in Academic Year of 2014/2015. The instrument of this research are syllabus, courseâs curriculum, student worksheets, post test, daily test, and 21st century skillâs observation sheet. Result of the research discovered that the application of Discovery Learning learning strategy is able to increase studentsâs 21st century skill. It shown by the raising of the 21st century skill scoreâs mean from the first cycle within 86,38% to 90% in the second cycle.Keywords : Discovery Learning, 21st Century Skill, Basic Microbiolog